Awareness of Environmental Change, Climate Variability, and Their Role in Prevalence of Mosquitoes among Urban Dwellers in Southern Ghana - Mattah, P.A.D.; Futagbi, G.; Mattah, M.M. (Journal of Environmental and Public Health, 2018)
This study evaluates the extent to which urban residents of Accra and Sekondi-Takoradi (all of southern Ghana) were aware of environment and climate-related variability. A total of 150 questionnaires were given to adults of 40 years and above who lived in the cities for at least 35 years. SPSS version 16 was used to process the data. Results show that all respondents in Accra Metropolitan Area (AMA) and 96% of them in Sekondi-Takoradi Metropolitan Area (STMA) noted the deteriorating vegetation cover over the cities. Similarly, 93% and 83% of them in AMA and STMA, respectively, observed that land use pattern of the two cities has changed considerably. There was positive and statistically significant correlation between respondents’ educational attainment and their awareness of changes in land use/land cover ( r=0.18 , n=140 , p=0.03 ). Also, 71% in AMA and 89% in STMA stated that temperature of the cities had been increasing over the years. In all, 82.9% of the respondents mentioned that they had problem with the increasing population of mosquitoes. Respondents demonstrated ample knowledge of environment and climate variability and should be engaged in preventing further environmental degradation. The top-down approach to environmental issues has failed; the bottom-up approach to environmental maintenance is needed.